Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1073/pnas.1523265113
|View full text |Cite
|
Sign up to set email alerts
|

A binding site outside the canonical PDZ domain determines the specific interaction between Shank and SAPAP and their function

Abstract: Shank and SAPAP (synapse-associated protein 90/postsynaptic density-95-associated protein) are two highly abundant scaffold proteins that directly interact with each other to regulate excitatory synapse development and plasticity. Mutations of SAPAP, but not other reported Shank PDZ domain binders, share a significant overlap on behavioral abnormalities with the mutations of Shank both in patients and in animal models. The molecular mechanism governing the exquisite specificity of the Shank/SAPAP interaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 74 publications
6
63
0
Order By: Relevance
“…In line with this, secondary structure predictions suggest one short helix and two β strands in the linker – the latter were also seen in the complex between Shank3 and an extended GKAP peptide (Zeng et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In line with this, secondary structure predictions suggest one short helix and two β strands in the linker – the latter were also seen in the complex between Shank3 and an extended GKAP peptide (Zeng et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…), as well as for an extended GKAP peptide in complex with the PDZ domain of Shank3 (Zeng et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Isothermal titration calorimetry (ITC)-based titration assay showed that N-terminal thioredoxin-tagged last 30 residues of SynGAP (SynGAP PBM) binds to each of the three PDZ domains with comparable and weak affinities (K d of a few dozens of micromolars; Figure 1G, G1). Such weak bindings are unlikely to support a specific functional interaction between SynGAP and PSD-95 in vivo (Ye and Zhang, 2013; Zeng et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The variant Arg536 (R536W) is positioned in the linker region between the SH3 domain and the PDZ domain of Shank3, but does not interfere with the binding of C-terminal ligands nor changes the overall structure of the SH3-PDZ tandem. [40] The implication of Shank3 in neurological disorder has promoted the development of inhibitors toward its PDZ domain. The PDZ domains of the Shank proteins are members of the class I PDZ domains, with a His positioned in the αB1 helix, which is proposed to bind primarily C-terminal ligands with a S/T-x-ϕ motif (Figure 8b,c).…”
Section: Targeting the Pdz Domain Of Src Homology 3 And Multiple Ankymentioning
confidence: 99%
“…[2] Several www.advancedsciencenews.com www.advtherap.com Figure 2. [40] In yet further distinctive binding mode variations of the canonical interaction, P 0 is buried deeper in the binding groove of the PDZ domain, occupying what corresponds to the P 1 position (Figure 2e). In a canonical insertion, there is a hydrogen bonding network (orange dashed lines) between the backbone of the PDZ domain and the backbone of the peptide.…”
Section: Introductionmentioning
confidence: 99%